Food forests: Their services and sustainability - Stefanie Albrecht; Arnim Wiek (Journal of Agriculture, Food Systems, and Community Development, 2021)
Industrialized food systems use unsustainable practices leading to climate change, natural resource depletion, economic disparities across the value chain, and detrimental impacts on public health. In contrast, alternative food solutions such as food forests have the potential to provide healthy food, sufficient livelihoods, environmental services, and spaces for recreation, education, and community building. This study compiles evidence from more than 200 food forests worldwide, with detailed insights on 14 exemplary food forests in Europe, North America, and South America, gained through site visits and interviews. We present and illustrate the main services that food forests provide and assess their sustainability. The findings indicate that the majority of food forests perform well on social-cultural and environmental criteria by building capacity, providing food, enhancing biodiversity, and regenerating soil, among others. However, for broader impact, food forests need to go beyond the provision of social-cultural and environmental services and enhance their economic viability. There is a need for specific trainings and other measures targeting this deficit. This study appraises the current state of food forests and provides an orientation for food entrepreneurs, public officials, and activists to better understand food forests’ potential for advancing sustainable food systems.